Restitution as an Instrument of Justice for Victims of Domestic Sexual Violence: A Study of Positive and Islamic Law in the Contemporary Era - Hendro Widodo; Anis Mashdurohatun; Kristiawanto; Andrianto Budi Santoso; Derick Yunanda (Faculty of Sharia, IAIN Metro, 2025)
Domestic sexual violence is a hidden form of gender-based crime that often goes unreported due to prevailing social norms and its status as a complaint-based offense. These conditions create serious obstacles to law enforcement and hinder victims from obtaining justice, ideally including immediate restitution and comprehensive protection from the state. This study explores the effectiveness of restitution as a criminal sanction in cases of domestic sexual violence, analyzed through the perspective of justice values in both positive law and Islamic law in the contemporary context. The research employs a normative juridical method, using a statutory approach by examining relevant legal instruments and Islamic legal principles. The findings reveal that although restitution is formally recognized in various laws—such as the Domestic Violence Law, the Law on Witness and Victim Protection, the Law on Sexual Violence Crimes (TPKS), and the 2023 Criminal Code—its enforcement remains limited. This is due to structural and cultural challenges, including weak legal awareness, ineffective implementation mechanisms, and the perpetrators’ inability to fulfill restitution obligations. From the perspective of Islamic law, the concept of compensation (Taʿwid) supports the idea of restoring victims' rights, but its application requires reinterpretation to fit the modern legal system. This study offers a new perspective by emphasizing the need to move beyond fines toward mandatory restitution, integrating restorative justice principles and strengthening institutional and cultural support. These steps are crucial for building a justice system that is more responsive, fair, and centered on the recovery and dignity of victims.